Oқыту мен оқу үрдісін жақсартудағы кері байланыстың әсері - Муканова, Ж.Ж. (My University, 2016)
In this article, author implies what should be paid attention in the process of comprehensive teaching and training and focuses on the role or giving feedback as the tool to improve the learning process. And stresses the need to take into account the peculiarities of giving feedback . At the end the author concludes with the types of feedback and shares its effective ways from her own experience.
Keywords: Effective teaching; Feedback; functional literacy; features; an experience